Metal Organic Framework-235 (MOF-235) Modified Carbon Paste Electrode for Catechol Determination in Water - Batista, Luiz Carlos Domingos; Santos, Thiago Izidoro Silva; Santos, José E. Lima; da Silva, Djalma Ribeiro; Martínez-Huitle, Carlos A. [UNESP] (Wiley, 2020)
MOF-235 is presented as an orange powder, with crystals of the octahedral formation. It was already used as adsorbent to remove different compounds from water; however, no attempts have been published about the exploration of the MOF-235 application as electrochemical sensor for organic compounds yet. MOF-235 was synthetized and after that, it was characterized by SEM, XRD and FTIR. Graphite electrodes (GEs) were modified with different MOF-235 ratio (5 %, 7 %, 10 %, 12 % and 14 %) and these modified GEs were characterized by cyclic voltammetry (CV) measurements in order to determine the effect of MOF-235 concentration on the current response. Results indicated that, a significant improvement on the current response was attained at MOF-235(10 %)/GE respect to unmodified GE. This behavior is related to the pore structure and multiple active sites on the MOF surface. The performance of the MOF-235(10 %)/GE as electrochemical sensor for detecting catechol was assessed by differential pulse voltammetry (DPV). Catechol detection response of MOF-based sensor provided a detection limit of about 12.79 μmol L−1 with a correlation coefficient (R2) of about 0.9928 ranging from 12 to 514 μmol L−1. Finally, MOF-235(10 %)/GE was used to determine catechol in real water matrixes.
Keywords: catechol, sensor, electrochemistry; graphite electrode; MOF-235